2017
DOI: 10.1002/lsm.22744
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment of treatment delivery for interstitial photodynamic therapy of high‐grade glioma in a preclinical model

Abstract: Ethical approval: This article contains studies using animals. All applicable institutional and national guidelines for the care and use of animals were followed. The experimental design was declared to the French National Ethics Committee under reference number 04870.01. Acknowledgments ObjectivesPrevious studies have reported the outcomes of PDT for glioblastoma via immunohistological data.Our study aimed to evaluate MRI findings, including diffusion and perfusion sequences, compared with immunohistological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Laser interstitial thermal therapy (LITT) has been used to treat a wide variety of diseases and disorders, such as epilepsy and tumors in the brain, breast, prostate, liver, and bone . Ablations using LITT can be used on its own, but also in, for example, conjunction with radiotherapy or after injection of light‐activated photosensitizer in photodynamic therapy . LITT is especially well suited for magnetic resonance imaging (MRI) guidance since the thin fiberoptic applicator and the catheter used for cooling fluid do not create large susceptibility artifacts in the MR images.…”
Section: Introductionmentioning
confidence: 99%
“…Laser interstitial thermal therapy (LITT) has been used to treat a wide variety of diseases and disorders, such as epilepsy and tumors in the brain, breast, prostate, liver, and bone . Ablations using LITT can be used on its own, but also in, for example, conjunction with radiotherapy or after injection of light‐activated photosensitizer in photodynamic therapy . LITT is especially well suited for magnetic resonance imaging (MRI) guidance since the thin fiberoptic applicator and the catheter used for cooling fluid do not create large susceptibility artifacts in the MR images.…”
Section: Introductionmentioning
confidence: 99%
“…PDT can directly affect cancer cells by inducing necrosis and/or apoptosis in the tumoral vasculature. 8 Some investigators have demonstrated the mode of action of PDT using functional magnetic resonance imaging 9 or optoacoustic imaging 10 in animal models. We would have clinically demonstrated the mode of action of PDT through the decreasing StO₂ levels after treatment in OS imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Primary effects of PDT are necrosis and apoptosis of tumor cells and the reduction of tumor vascularization. Our previous preclinical studies allowed us to compare MRI volumes with histological samples [24][25][26]. Using these results, we demonstrated that diffusion MRI is a marker of cell death, perfusion MRI indicates the level of necrosis and T2 sequences enhance strongly the peritumoral edema of tumors.…”
Section: Follow-upmentioning
confidence: 90%